ASSISTANCE FOR COMMUNITY GROUP THROUGH ENVIRONMENTAL HEALTH EDUCATION IN SANCA VILLAGE, CIATER DISTRICT, SUBANG REGENCY - Riany L Nurwulan; Abu Huraerah (Jurnal Scientia, 2023)
Community service with the theme of assisting community groups through environmental health education aims to support efforts to realize environmental health in the community in Sanca Village, Ciater District, Subang Regency. Environmental health is an important aspect of environmental management because with good environmental management, environmental health will be achieved. Such conditions can be achieved if there is good behavior from the community related to environmental health. That's why environmental health education is needed for the community, both for children and adults. Things that need to be educated include household waste management, namely regarding sorting and disposing of waste, hygiene behavior. disposal of dirty water/waste, and cleanliness of the environment around the house, so that people can implement clean and healthy living behaviors (PHBS) which include environmentally friendly behavior and hygienic behavior In connection with the PKM activities organized by FISIP UNPAS, the community that is used as a partner in implementing the PKM is the community of Sanca Village, Ciater District, Subang Regency. The partner is the PKK Group in Sanca Village, Ciater District, Subang Regency. The main problem experienced by partners is that there are still some people who hold old habits in their health behavior that pay little attention to environmental health. The method used in implementing the activity is locality development, (local community development method), with a focus on environmental health assessment. The technique used to support the realization of the activity is the transect walk. The results of the assessment implementation are used as a basis for the activity implementing team in determining action plans, namely activities that can be carried out in the area by the activity implementing team. As for the action plan for the activity implementing team is to provide assistance regarding environmental health education for the community through environmental health counseling and providing assistance with environmental cleaning tools.